More iPhone Cool Projects Cool Developers Reveal the Details of their Cooler Apps - Smith, Ben; Chin, Danton; Palm, Leon; Smith, Dave; Smith, Charles; Hoefele, Claus; Mora, Saul; de Vries, Arne; van de Wijgerd, Joost; Penberthy, Scott; Kazez, Ben; Smith, Roderick; et al. (Apress : Imprint: Apress, 2010)
Everyone is developing iPhone applications, and it's clear why. The iPhone is the coolest mobile device available, and the App Store makes it simple to get an application out into the unstoppable iPhone app market. With hundreds of thousands of app developers entering the game, it's crucial to learn from those who have actually succeeded. This book shows you how some of the most innovative and creative iPhone application developers have developed cool, best-selling apps. Not only does every successful application have a story, but behind every great app is excellent code. In this book, you'll see the code and learn how to use it to make your own cool applications. You'll learn everything from importing 3D art assets into your iPhone game to using Cocos2d for iPhone and iPad. This book shares the secrets of the coolest iPhone apps being built today by the best iPhone developers-invaluable knowledge for anyone who wants to create the app that everyone is talking about.